Innovation and the micro-enterprise. (1st January 2001) - Simpson, Barbara
Small and medium sized enterprises (SMEs) have increasingly been placed under the scholarly microscope, particularly with respect to their capacity for innovation. But how small is small? This paper is concerned with micro-enterprises (those employing fewer than 20 people) which, although they exist in tremendous numbers worldwide, remain largely unexplored by organisational scholars. Using New Zealand micro-enterprises as an illustration, this paper advocates a cognitive approach to developing a greater understanding of innovation in this important class of organisations.